A Brief Talk on Translation Issues About Country-Specific Chinese Teaching Material for Indonesia - Kelly Rosalin (Humaniora, 2014)
Currently, the majority of Chinese teaching materials used in Indonesia has general characteristic usage, and poorly addresses the true needs of Indonesia students. The Chinese teaching materials used in Indonesia are not country-specific but only translated into Indonesian language. This paper evaluated six books, consisting three types of elementary Chinese teaching materials thoroughly observed Indonesian language translation, and analyzed translation issues that occur in the Chinese language teaching materials. Through this observation, it can be seen in translation aspect, still not appropriate for Indonesian students.